Formation of Orthogonal Controlled Value Components in Micro-Processor Protection of Power Reducing Transformer - F. A. Romaniuk; M. S. Loman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper considers formers of orthogonal components of the first, second and fifth current harmonics. The formers are made on the basis of the Goertzel algorithm. The paper also contains investigations of frequency and dynamic properties of these formers.